Spiritual Healing: A Study of Modern Sufi Reflexology Therapy in Indonesia - Mohammad Rindu Fajar Islamy; Yedi Purwanto; Usup Romli; Alwan Husni Ramdani (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
There have been advances achieved in modern medicine but traditional treatment methods using certain spiritual approached have become increasingly popular in many parts of the world. Certain Sufi practices, among others, is used in medical treatment to support the healing process. Based on a case study on the practice of Sufi therapy conducted by Akang Syamsudin in the Limbangan Garut area, West Java, Indonesia this article attempts to explore the conversion process and dynamics of the development of Sufi healing. Employing a qualitative approach and Miles and Huberman landscape approach, and supported with interviews, observations, and documentation the research finds that Syamsudin’s Sufi therapy method combines physical and spiritual principles. Syamsudin’s therapeutic approach is based on the following seven factors, are: 1) belief that every disease has a cure; 2) balance and moderation are directly proportional to physical health; 3) spiritual factors dominate over physical factors; 4) the importance of blood circulation; 5) the efficacy of positive suggestion; 6) belief and submission to God’s will; 7) the effectiveness of patience and consistency. The research implications open a new paradigm in the field of non-invasive treatments. This article suggests that modern medical treatment should be complemented with spiritual therapy in order to achieve more positive healing outcomes for patients.